Health Information Exchange and Ambulatory Quality of Care - Kern, L.M.; Barrón, Y.; Dhopeshwarkar, R.V.; Kaushal, R. (Applied Clinical Informatics, 2012)
Background: Health information exchange is a national priority, but there is limited evidence of its effectiveness.Objective: We sought to determine the effect of health information exchange on ambulatory quality.Methods: We conducted a retrospective cohort study over two years of 138 primary care physicians in small group practices in the Hudson Valley region of New York State. All physicians had access to an electronic portal, through which they could view clinical data (such as laboratory and radiology test results) for their patients over time, regardless of the ordering physician. We considered 15 quality measures that were being used by the community for a pay-for-performance program, as well as the subset of 8 measures expected to be affected by the portal. We adjusted for 11 physician characteristics (including health care quality at baseline).Results: Nearly half (43%) of the physicians were portal users. Non-users performed at or above the regional benchmark on 48% of the measures at baseline and 49% of the measures at follow-up (p = 0.58). Users performed at or above the regional benchmark on 57% of the measures at baseline and 64% at follow-up (p<0.001). Use of the portal was independently associated with higher quality of care at follow-up for those measures expected to be affected by the portal (p = 0.01), but not for those not expected to be affected by the portal (p = 0.12).Conclusions: Use of an electronic portal for viewing clinical data was associated with modest improvements in ambulatory quality.
Keywords: Health care quality; clinical informatics; quality indicators